STRATEGIES TO ENHANCE PEER FEEDBACK AND SELF ASSESSMENT IN EXTENDED SPEAKING COURSE - Khusnia, Aulia Nisa (PEOPLE: International Journal of Social Sciences, 2015)
This study explores ways to engage students in peer feedback and self-assessment on different aspects of their work, from in-class activities to essays, problem sets and presentations in extended speaking course, English education, faculty of teacher training and education, The University of Muhammadiyah Purwokerto, Indonesia. Sharing the process of giving and receiving feedback with students is beneficial for the learning process as it enables students to take greater ownership of their learning and develop their critical thinking and feedback skills. A crucial factor in the effective use of self-assessment and peer feedback is to ensure that you introduce the idea to students early on in their course. In addition, it is useful to discuss, and revisit regularly, the purpose of the self-assessment or peer feedback activity, to encourage students to view it as an integral part of their learning